How the 2008-2009 financial crisis shaped fair value accounting literature: A bibliometric approach - Carlos Sampaio; Luís M. Carmo Farinha; Jo\~ao Renato Sebasti\~ao; Mónica Régio (Administrative Sciences, 2022)
This study aims to fulfil a gap in the literature, delivering a road map to understand the course and nature of the fair value accounting literature, further showing how the 2008-2009 financial crisis affected it. Bibliometric methods analyze 377 documents retrieved from the Web of Science and Scopus databases. Results show a heavy increase in fair value accounting literature starting due to the 2008-2009 financial crisis, further showing a shift from fair value accounting regulations to topics such as fair value measurement, earnings management, value relevance, and banks. Results provide further evidence about relevant themes, showing that topics related to financial crises stay relevant, even during times of growth.
Keywords: 350; accounting; fair value; financial crisis; IFRS; SFAS